Analyzing Brand Revival Strategies Using a Meta-Synthesis Approach - karim majeed, Diar; Sheikhesmaeili, Saman; Soltan Panah, Hirsh (Management Strategies and Engineering Sciences, 2025)
In today's world, a dynamic economy and intense competition in the business arena have increasingly challenged brands. Among them, legacy brands that once dominated the market gradually lose their position and may even be forgotten by consumers. To prevent this and maintain their market share, many of these brands turn to brand revival strategies. The objective of these strategies is to restore the lost credibility and popularity of the brand and to re-establish a connection with customers. This is achieved through the renewal and reconstruction of brand identity, the introduction of new and appealing products and services, and the adoption of innovative marketing and advertising methods. In essence, brand revival is an effort to return to the peak of success and re-enter market competition. The present study aimed to examine brand revival strategies using a meta-synthesis method. In this regard, employing the seven-stage method of Sandelowski and Barroso, the required data were extracted from scientific and research articles published over a 24-year period (1990-2014). Following an initial review, 24 articles were selected for in-depth analysis. The extracted data were analyzed using MAXQDA 2020 software based on the conceptual model of the study. The results of this analysis led to the identification of 94 sub-strategies, which were categorized into seven main strategies. The primary brand revival strategies encompass various aspects, which can be broadly classified as follows: brand identity and image management to clarify and enhance audience perception of the brand, product renewal and development to meet contemporary market demands and attract new customers, integrated marketing to ensure consistency and alignment across all marketing and advertising activities, customer relationship management to establish a sustainable and effective connection with customers and increase their satisfaction, market repositioning to define an appropriate competitive position for the brand and attract target customers, brand heritage and authenticity management to preserve and enhance the historical and cultural values of the brand, and finally, organizational change management to implement necessary modifications in the organizational structure and processes to support brand revival strategies.